Metacognitive Strategies of Developing the Reading Competence of Students of Institutions of Higher Education - Тамілія Доцевич (Психолінгвістика, 2019)
Introduction. The paper presents the peculiarities and advantages of using the metacognitive strategies to develop the reading competence in students of pedagogical universities in the process of educational-vocational training; the notion “strategies of reading” is clarified, the basic structural components are determined; the functions of the metacognitive strategies, their role when working with scientific texts are considered. The theoretical approaches to the metacognitive strategies are represented, their functions, their role in understanding scientific texts. The notions and meanings of the metacognitive skills and metacognitive strategies are revealed. The metacognitive skills can be considered as an integration of the ability to understand scientific texts and metalinguistic erudition, i. e. as a set of knowledge about the text and ability to work with the text. The paper presents the author’s programme of forming metalinguistic strategies when working with scientific texts.